American Medical Center for Burma records - American Medical Center for Burma
Correspondence, subject files, administrative and financial records, magazines, clippings, maps, and other records relating chiefly to Namkhan Hospital and the Midwives and Nurses Training School at Namkhan, Burma, run by Dr. Gordon Stifler Seagrave, known as the "Burma surgeon." Subjects include American foreign policy, Dr. Thomas A. Dooley, Peace Corps (U.S.), and the political situation in Burma. Correspondents include Rothwell H. Brown, Fanny McConnell Ellison, John Scott Everton, David McKendree Key, Joseph F. Newhall, Ruth Newhall, Barbara Olmanson, Myron Donald Olmanson, Harold L. Oram, R.S. Radvin, Haldor Reinholt, John F. Rich, Howard P. Wilson, Gordon Stifler Seagrave, his wife, Marion Seagrave, and their son, Sterling Seagrave.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Organization incorporated in 1946. Based in New York to support Gordon Stifler Seagrave and the Namkhan Hospital in Burma.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown, Rothwell H. -- Correspondence; Dooley, Thomas A. -- 1927-1961.; Ellison, Fanny McConnell -- Correspondence; Everton, John Scott -- Correspondence; Key, David McKendree, -- 1900-1988 -- Correspondence; Newhall, Joseph F. -- Correspondence; Newhall, Ruth -- Correspondence; Olmanson, Barbara -- Correspondence; Olmanson, Myron Donald -- Correspondence; Oram, Harold L., -- 1907-1990 -- Correspondence; Radvin, R. S. -- Correspondence; Reinholt, Haldor -- Correspondence; Rich, John F. -- Correspondence; Seagrave, Gordon Stifler, -- 1897-1965.; Seagrave, Gordon Stifler, -- 1897-1965 -- Correspondence; Seagrave, Marion -- Correspondence; Seagrave, Sterling -- Correspondence; Wilson, Howard P. -- Correspondence; Midwives and Nurses Training School (Namkhan, Burma); Namkham Hospital; Peace Corps (U.S.); Hospitals -- Burma -- Namkhan; Medicine -- Burma -- Namkhan; Nurses -- Burma -- Namkhan; Burma -- Politics and government; Namkhan (Burma) -- History; United States -- Foreign relations -- 20th century